MAHASISWA MEROKOK DAN TIDAK MEROKOK DI LINGKUNGAN STIKES SURYA GLOBAL YOGYAKARTA - Dedy Kuswoyo (STIKes Surya Global Yogyakarta, 2017)
Background: Smoking behavior has increased from 34.2% in 2007 to 36.3% in 2013, thus, it is predicted that it will boost to 1.6 milliar smoker in 2020 if the smoking cessation program fails. The high prevalence of smoking behavior is also found even in Islamic countries. Despite the understanding of Islamic value, thus, it requires an individual commitment to stop smoking. Meanwhile, the majority of students (90%) in Islamic Boarding House (Pesantren) Stikes Surya Global of Yogyakarta Special Region do not possess smoking behavior. Therefore, the main and supporting factors that influence non-smoking behavior in this Islamic environment need to be understood. Objective: This study aims to investigate the main and supporting factors involved in this nonsmoking behavior in Islamic Boarding House (Pesantren) Stikes Surya Global of Yogyakarta Special Region. Methods: This study was designed as a qualitative research with phenomenology approach to evaluate and analyze in-depth the non-smoking behavior among students from Islamic Boarding House (Pesantren) Stikes Surya Global in Yogyakarta, taken by maximun variation sampling technique. The variation included non-smoker status, former smoker, lecturer/murabbi and leader of pesantren/amir. Data were taken with in-depth interview and focus group discussion (FGD) following previous observation. Data validation was performed with data triangulation, using informant data from students, murabbi, and amir. Results: The major factor affecting non-smoking behavior is the knowledge on smoking law according to Islam, the non-smoker informant believe that smoking is haram or forbidden whereas the smoker informant ensure that smoking is makruh or permitted but not recommended. Reinforcing factor affecting non-smoking behavior is the influence of program held by the boarding House or pesantren, social interaction in the House and role-model factor from the leader/amir of this Islamic boarding house. Conclusion: The factors affecting non-smoking behavior in Islamic Boarding House Stikes Surya Global of Yogyakarta Special Region is the knowledge and beliefs on Islamic taught on smoking, supported by the school’s programs, social interaction and role-model from the leader/amir.